Pendampingan Kelompok Tanggap Bencana dengan Pendekatan Fikih Kebencanaan Sebagai Mitigasi Bencana Alam di Desa Batu Beriga, Kabupaten Bangka Tengah - Desfa Yusmaliana; Fadillah Sabri; Fifin Fitriana (Jurnal Pengabdian Pada Masyarakat, 2022)
Bangka Island is a tin mining area and has the potential for natural disasters due to these mining activities such as drought, erosion, and sedimentation disasters. The Islamic perspective must be contemplated further to understand and address every incident proportionally in interpreting and responding to disasters. The Tarjih Council and Tajdid Muhammadiyah have formulated disaster fiqh that must be conveyed, primarily through youth organizations consisting of the youth of the nation's generation as part of the service program. Furthermore, these youth groups are referred to as "Disaster Response Groups" so that they can be used as daily guidelines and a guide to avoiding behaviors that can damage the environment and lead to disasters. Assistance for disaster response groups through reactivation of youth organizations facilitates youth in Batu Beriga Village, Kec. Lubuk Besar, Kab. Central Bangka understands the concept of disaster and disaster mitigation with a disaster fiqh approach. It is intended that these teenagers are trained to respond to natural phenomena that arise and respond to them positively and correctly. The method used in this service is socialization and the formation of a Disaster Response group, and Assistance in preparing structures, main tasks, simulation programs, and evaluation. The results show that the Assistance of disaster response groups increases youth awareness about disaster mitigation through 3 aspects: understanding of disaster mitigation with a disaster jurisprudence (fikih) approach, development of disaster response groups, and skills on disaster mitigation.